1993
DOI: 10.1038/bjc.1993.265
|View full text |Cite
|
Sign up to set email alerts
|

Weekly chemotherapy in advanced prostatic cancer

Abstract: Summary This randomised phase II study was performed in order to evaluate the effectiveness of a weekly chemotherapy regimen in advanced prostatic carcinoma patients (stage D2) refractory to hormonal therapy. Seventy-two cases were studied: they were randomised in a 2:1 ratio to receive either epirubicin (30 mgm 2 weekly) or doxorubicin (25 mg m weekly); 48 patients received epirubicin and 24 received doxorubicin.After 12 courses of chemotherapy, the 45 evaluable patients in the epirubicin arm showed a respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…We documented a palliative response rate of 48% and a median duration of response of six months, which compare favourably with the results obtained using other first-line cytotoxic drugs (table 2) [7, 8, 9, 19]. However, these preliminary results must be confirmed in the setting of a currently on-going phase III trial, which includes the study of the optimal dosage: a weekly vs. a 3-weekly schedule.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We documented a palliative response rate of 48% and a median duration of response of six months, which compare favourably with the results obtained using other first-line cytotoxic drugs (table 2) [7, 8, 9, 19]. However, these preliminary results must be confirmed in the setting of a currently on-going phase III trial, which includes the study of the optimal dosage: a weekly vs. a 3-weekly schedule.…”
Section: Discussionsupporting
confidence: 81%
“…Doxorubicin has shown some activity in the treatment of patients with HRPC, and epirubicin (the 4′ epimer of doxorubicin) has proved to be effective in improving bone pain and performance status when administered alone or as part of a combination treatment [9, 10, 11]. Recent randomised trials have demonstrated better symptom palliation with the mitoxantrone+steroid combination than either prednisone or hydrocortisone [8, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the patients with bone metastasis were studied repeatedly. At each sampling time, the patients with bone metastasis were evaluated based on the finding of bone scan compared with the previous bone scan with information of symptom change, PSA value and/or other imaging modalities; new (NEW), complete remission (CR), improvement (IMP), flare-up (FLARE), no change (NC) and progression of disease (PROG) based on national prostatic cancer project response criteria (Slack and Murphy, 1984;Francini et al, 1993). NEW indicates newly diagnosed bone metastasis.…”
mentioning
confidence: 99%
“…The EORTC Genitourinary Group (protocol 30841) used EPR 12 mg m-2 weekly with an objective response rate (complete or partial) of only 12% (Jones et al, 1987). Francini et al (1993) presented a 37.7% response rate (bone scan, soft-tissue metastases, acid phosphatase, weight, symptoms and performance status) after EPR 30 mg m-2 weekly, and Elomaa et al (1991) demonstrated improved performance status in 69% of patients using EPR at 25 mg m-2 weekly. In order to increase efficacy, but still within a level of tolerable toxicity, higher doses of EPR have been tested.…”
Section: Toxicitymentioning
confidence: 98%